Knowledge, perception and practice of local delivery antibiotics in management of periodontal diseases - Izaddin, Ameerah Dianah; Ahmad Subhi, Siti Farah Amelia; Muhammad Ali, Suhaila; Yaacob, Munirah; Ardini, Yunita Dewi (2018)
Introductions: Local delivery antibiotic (LDA) is adjunctive to mechanical debridement for periodontal disease therapy. However, no work has published on the relationship between knowledge, perception and practice (KPP) with periodontist. The objective of this research is to determine the present status of the periodontists’ KPP on the use of LDA in management of periodontal diseases. Materials and methods: This research was a cross-sectional study among universities periodontists in Malaysia. Self-administered online questionnaires were distributed through email. The data was analyzed by using Statistical Package for Social Sciences (SPSS) Version 24. IREC approval was obtained (ID: IREC 674). Results: A total of 17 periodontists participated in this study. Majority of them were from government universities (53%), overseas graduated (71%) and practiced for 10 years or less (53%). 77% of the periodontists were aware on the availability of LDA in Malaysia. All respondents agreed the importance of LDA as adjunctive treatment. However, only 47% of the periodontists practiced LDA in managing periodontal diseases. 57% of respondents claimed the LDA cost is expensive. Conclusion: Periodontists had adequate knowledge and perception of LDA with less practice.